Effect of external pressure on the structural stability, electronic structure, band gap engineering and optical properties of LiNbO3: An ab-initio calculation. (June 2020) - Gillani, S.S.A.; Ahmad, Riaz; Zeba, I.; Islah-u-din,; Shakil, M.; Rizwan, Muhammad; Rafique, Muhammad; Sarfraz, M.; Hassan, S.S.
Highlights: A comprehensive study of influence of external pressure on structural, electronic and optical properties of LiNbO3 . Static refractive index increases with the increase of pressure. Slight shifting of absorption edge to lower energies with external pressure. Beyond 25 GPa external pressure stability of the structure degrades. Electronic structure and optical properties correlate very well. Abstract: A detailed theoretical investigation to explore the effects of external pressure (0.0GPa, 2.5GPa, 5.0GPa, 7.5GPa, 10GPa, 12.5GPa, 15GPa, 17.5GPa, 20GPa and 25GPa) on structural stability, electronic structure, band gap engineering and its impact on optical properties in LiNbO3 by using CASTEP code, based on ab-initio density functional theory, with ultra-soft pseudopotential and exchange correlation functional GGA-PBE, is presented. From band structure, it is observed that the top of the valence band is typically controlled by O-2p and Nb-4d orbital electrons and the band gap exhibits nearly linear decreasing trend (3.542eV–2.905eV) with the increasing external pressure. Decreasing trend of the electronic band gap with increase of external pressure is explained with the help of total density of states and elemental partial density of states. Moreover, with the increase of external pressure beyond 25 GPa stability of the structure degrades significantly. In addition, to study the impact of band gap reduction on the optical properties, we have also calculated the refractive index, the reflectivity, absorption function and the energy loss function of the LiNbO3 by the complex dielectric function under various external pressures. The optical results reveal that the static refractive index increases with the increase of pressure and the variation ranges of the absorption function and the reflectivity rate are also broadened. Absorption spectra, under increase of pressure, show the red shift and the major plasmon peaks display blue shift, which is the thumb proof of electronic band gap reduction. Both the electronic structures and optical properties of LiNbO3 can be constructively tempered with pressure, which contributes an effective theoretical basis for the further application of the LiNbO3 under pressure.